2013
DOI: 10.1111/iej.12120
|View full text |Cite
|
Sign up to set email alerts
|

Influence of powder‐to‐water ratio on radiopacity, setting time, pH, calcium ion release and a micro‐CT volumetric solubility of white mineral trioxide aggregate

Abstract: The ratio of powder/water significantly interfered with the physical and chemical properties of white MTA Angelus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
130
2
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(159 citation statements)
references
References 21 publications
12
130
2
15
Order By: Relevance
“…Atomic absorption spectrophotometry has been used successfully in earlier studies for analyzing calcium ions, 15,16 whereas the setting time evaluation using Gillmore needles is a standard test method that has been used previously to evaluate the setting time of MTA-based materials. 15,17 In the present study, W-MTA showed the highest pH values. It is well-established that MTA promotes an alkaline pH in a physiological solution.…”
Section: Discussionsupporting
confidence: 52%
“…Atomic absorption spectrophotometry has been used successfully in earlier studies for analyzing calcium ions, 15,16 whereas the setting time evaluation using Gillmore needles is a standard test method that has been used previously to evaluate the setting time of MTA-based materials. 15,17 In the present study, W-MTA showed the highest pH values. It is well-established that MTA promotes an alkaline pH in a physiological solution.…”
Section: Discussionsupporting
confidence: 52%
“…MTA is a bioactive dental material and a calciumreleasing cement [10][11][12] . Although the release of calcium ions from MTA may cause an interaction between MTA and the surrounding tissues, the pathway by which CaSR contributes directly to the regulation of osteoblast differentiation via calcium ion released from MTA remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the calcium hydroxide dissociates into calcium and hydroxide ions, which disperse into the surrounding environment, resulting in MTA bioactivity 7) . Some in vitro studies have indicated that calcium ions are released continuously from MTA [10][11][12] . Takita et al reported that the release of ions from MTA provides the optimum amount of calcium for the proliferation and migration of dental pulp cells 4,13) .…”
Section: Introductionmentioning
confidence: 99%
“…A proporção pó/líquido pode alterar o pH e a liberação de íons cálcio do MTA (CAVENAGO, et al, 2013). A adição de maiores proporções de líquido na mistura resulta em aumento do pH e da liberação de cálcio.…”
unclassified
“…A adição de maiores proporções de líquido na mistura resulta em aumento do pH e da liberação de cálcio. Este fenômeno pode estar relacionado com a maior solubilização do cimento (CAVENAGO, et al, 2013 …”
unclassified